Effects of thermal therapy combined with blue light‐emitting diode irradiation on trimellitic anhydride-induced acute contact hypersensitivity mouse model. (3rd April 2022) - Piao, Chun Hua; Fan, Yan Jing; Nguyen, Thi Van; Song, Chang Ho; Jeong, Hwan-Jeong; Chai, Ok Hee
Abstract: Backgroud: The biological effect of phototherapy, which involves using visible light for disease treatment, has attracted recent attention, especially in dermatological practice. Light-emitting diode (LED) irradiation increases dermal collagen level and reduces inflammation. It has been suggested that thermal therapy and LED irradiation can modulate inflammatory processes. However, little is known about the molecular mechanism of the anti-inflammatory effects of thermal therapy and LED irradiation. Objective: This study was to determine the anti-inflammatory effect of thermal therapy combined with LED irradiation on trimellitic anhydride (TMA)-induced acute contact hypersensitivity (CHS) mouse model. Methods: Twenty-four BALB/c mice were randomly divided into the following groups: Vehicle group, TMA group, TMA + alternating thermal therapy group (Alternating group), and TMA + alternating + LED group (LED group). Ear swelling was measured based on the thickness of ear before and after each TMA challenge. Vascular permeability was evaluated by the extravasation of Evans blue dye. Serum IgE level, Th1/Th2/Th17 cytokines, and related transcription factors were measured using ELISA kits, and histological examination was illustrated in ear tissue. Results: The LED group showed reduction in ear swelling response, vascular permeability, serum IgE levels, Th2/Th17 cytokine levels, and inflammatory cell infiltration. Moreover, the LED group showed increased Th1 cytokine levels. Conclusions: These results indicate that thermal therapy combined with LED irradiation alleviated TMA-induced acute CHS in the mouse model. Thermal therapy and phototherapy should be considered as a novel therapeutic tool for the treatment of skin inflammation.